RESEARCH IN MATHEMATICS EDUCATION FROM A PHENOMENOLOGICAL PERSPECTIVE: "CHANGE IN THE TEACHING PRACTICE OF THE MATHEMATICS TEACHER" - BICUDO, Maria Aparecida Viggiani; HIRATSUKA, Paulo Isamo (Studia Universitatis Babeș-Bolyai Philosophia, 2015)
The goal of this study was to investigate change in the teaching practice of the mathematics teacher, adopting a qualitative research approach from a phenomenological perspective. Our understanding of phenomenological research, and the fundamental ideas underlying it, is presented. The research is described, including the ideographic and nomothetic analyses, and the six invariants, or open categories that emerged. We present our interpretation of one of them, the possibilities of going through the experience: loosening the ties to the past and an objective look at change.